Mempertahankan Eksistensi Media Cetak Di Tengah Gempuran Media Online - I Made Suyasa; I Nyoman Sedana (Jurnal Komunikasi dan Budaya, 2020)
The development of information and communication technology has brought a large flow of changes to the media industry, especially print media. The proliferation of online media is a threat to conventional media. In this digital age, information and news are more easily obtained from various online sources. This condition has caused a number of print media industries in the country to "shut down" because of their inability to seize the market. On the other hand, a number of print media industries are currently trying to adapt in the midst of the rapid development of information and communication technology by migrating to a digital platform, but still maintaining its print version.